'Template-free' synthesis of self-assembled micro-spikes resulting in 'sea-urchin'-like carbon structures for suppressing electromagnetic radiation. Issue 20 (15th August 2022) - M. P., Vidyashree; Sushmita, Kumari; M. K., Kokila; Bose, Suryasarathi
Abstract : We report the facile 'template-free' synthesis of self-assembled 'micro-spikes', resulting in sea-urchin-like carbon structures that can suppress incoming electromagnetic (EM) radiation, which is not achievable with conventional flake-type dispersed composites. Abstract : We report the facile 'template-free' synthesis of self-assembled 'micro-spikes', resulting in sea-urchin-like carbon structures that can suppress incoming electromagnetic (EM) radiation, which may not be achievable with conventional flake-type dispersed composites. Herein, we synthesized 'carbon-urchins' (C-urchins) from the self-assembly of short carbon fibers (CFs) via a facile one-pot synthesis method and then incorporated them into an epoxy matrix to obtain high-performance EMI shielding materials. To gain mechanistic insight, the C-urchins were doped with different dopants, such as magnetic nano-Fe3 O4 (C-F urchins), conducting nano-Ag particles (C-A urchins), and dielectric nano-SiO2 (C-S urchins), to evaluate the influence of the dopant on the EMI shielding performance. Interestingly, all three doped C-urchin types in an epoxy matrix showed excellent absorption-dominated shielding (>99%) in the K-band region, with shielding effectiveness (SET ) of up to −32 dB. The spatial distribution of the C-urchins was controlled in the epoxy composites to achieve the highest SET values for the prepared composites. The thermal properties of the composites were similar to those of neat epoxy; however, the storage modulus was enhanced in the composites. To this end, while high loading of conducting filler is required to meet commercial standards, resulting in processing difficulties, C-urchin-filled composites can open up new avenues in this field. The micro-spikes of the C-urchins can scatter/absorb incoming EM radiation through coupling with the fields.